Speciation genomics and a role for the Z chromosome in the early stages of divergence between Mexican ducks and mallards. Issue 21 (21st October 2015) - Lavretsky, Philip; Dacosta, Jeffrey M.; Hernández‐Baños, Blanca E.; Engilis, Andrew; Sorenson, Michael D.; Peters, Jeffrey L.
Abstract: Speciation is a continuous and dynamic process, and studying organisms during the early stages of this process can aid in identifying speciation mechanisms. The mallard ( Anas platyrhynchos ) and Mexican duck ( A . [ p .] diazi ) are two recently diverged taxa with a history of hybridization and controversial taxonomy. To understand their evolutionary history, we conducted genomic scans to characterize patterns of genetic diversity and divergence across the mitochondrial DNA (mtDNA) control region, 3523 autosomal loci and 172 Z‐linked sex chromosome loci. Between the two taxa, Z‐linked loci (ΦST = 0.088) were 5.2 times more differentiated than autosomal DNA (ΦST = 0.017) but comparable to mtDNA (ΦST = 0.092). This elevated Z differentiation deviated from neutral expectations inferred from simulated data that incorporated demographic history and differences in effective population sizes between marker types. Furthermore, 3% of Z‐linked loci, compared to <0.1% of autosomal loci, were detected as outlier loci under divergent selection with elevated relative (ΦST ) and absolute (dXY ) estimates of divergence. In contrast, the ratio of Z‐linked and autosomal differentiation among the seven Mexican duck sampling locations was close to 1:1 (ΦST = 0.018 for both markers). We conclude that between mallards and Mexican ducks, divergence at autosomal markers is largely neutral, whereas greater divergence on the Z chromosome (or some portions thereof) is likely the product of selection that has been important in speciation. Our results contribute to a growing body of literature indicating elevated divergence on the Z chromosome and its likely importance in avian speciation.